Set-up for spontaneous and induced birefringence measurements - Ciżman, Agnieszka; Poprawski, Ryszard (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The paper presents a simple polarization-interference set-up for demonstration of temperature dependence of birefringence and both electrooptical phenomena which can be used for the students laboratory and scientific investigation.
Optica Applicata, Vol. 35, 2005, nr 1, s. 163-170
Keywords: optyka; birefringence; ferroelectric material